Environmental planning policy and development strategies in the context of Maqasid Al-Shari’ah - Abu Bakar, Salwahiddah; Ahmad Sarkawi, Azila; Abdullah, Alias (American Scientific Publishers, 2017)
In general, town and country planning are dominated by policies and strategies. These policies are most likely to vary according to the scale, type and purpose of the planning. Malaysia exercises a three-tier planning system which is attached to physical plans namely, National Physical Plan, State Structure Plan and Local Plan as well as Special Area Plan. The aim of the study is to assimilate policies in the Pahang State Structure Plan and the development strategies in the Kuantan Local Plan, which are related to environmental planning in line with the five essential aspects of Maqasid al-Shari’ah, notably the preservation of faith, self, intellect, lineage and property; Maqasid al-Shari’ah is the objectives of Islamic law. On February 10 2015, the government of Malaysia conducted the Malaysia Shari’ah Index and the result was released a year later. Among the seven sectors, the infrastructure and environment sector scored the lowest. In this regard, using content analysis and an expert interview were used to compare policies and development strategies with the five essentials of maqasid. The study found that there were more policies and strategies on preserving property while faith ranked the lowest. This unbalanced score means that the preservation of property was more emphasised compared to other aspects in the environment planning policies and strategies in the Pahang State Structure Plan and Kuantan Local Plan. Thus, it is desirable to develop more policies and strategies for environmental planning.